Knowledge and compliance on alendronate sodium among osteoporosis patient in Hospital Sultanah Bahiyah, Kedah - Mahamud, Mufidah Haikal; Ismail, Isma Anati (2013)
It is estimated that over 200 million people worldwide have osteoporosis. The prevalence of osteoporosis is continuing to escalate with the increasingly elderly population. There are several different treatments for osteoporosis, including healthy lifestyle and a variety of medications. This study focuses on the knowledge and compliance of the osteoporosis patient towards alendronate sodium which is use to treat osteoporosis. This study was conducted at Outpatient Pharmacy Department, Hospital Sultanah Bahiyah from October 2012 to February 2013. A total of 54 visitors completed the survey and included in analysis. Other than that, the telephone interview was also carried out to some of the patients that didn’t come to the hospital. Data was analyzed and tabulated using both SPSS version 15.0 and Microsoft Excel 2007. From the result, most of them are very compliance with the alendronate sodium. Although some of them didn’t know about the precaution and how to administer the drug in a correct ways, they follow all of the instructions that give by the doctor or the pharmacist.